Synthesis of Allenyl Esters by Horner–Wadsworth–Emmons Reactions of Ketenes Mediated by Isopropylmagnesium Bromide - Sano, Shigeki; Matsumoto, Tomoya; Yano, Teppei; Toguchi, Munehisa; Nakao, Michiyasu (Synlett, 2015)
The synthesis of conjugated allenyl esters (tri-substituted allenes) was achieved by magnesium(II)-mediated Horner–Wadsworth–Emmons reaction of methyl bis(2,2,2-trifluoroethyl)phosphonoacetate with disubstituted ketenes. In addition, a novel access to α-fluorinated allenyl carboxamides (tetrasubstituted allenes) is presented.
Keywords: Horner–Wadsworth–Emmons reaction; allenes; ketenes; Grignard reagents; fluorine